Cartel Formation with Endogenous Capacity and Demand Uncertainty - Johannes Paha (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This article provides a framework for the analysis of cartel formation. It models the strategic interaction among firms who invest into production capacity, sell a near-homogeneous good, and are subject to unexpected demand shocks with persistence. The firms either compete or collude in prices. The model shows that a reduction of demand may promote collusion despite lowering collusive profits. This is the case when capacities are durable and a perceptible decline in demand creates excess capacities that make competition more intense. One finds unstable cartels especially for low discount rates as these lead the firms to choose asymmetric capacities.
Keywords: D43; L11; L41; 330